Epileptic manifestations induced by midazolam in the neonatal period - Montenegro,Maria Augusta (2001)
Antiepileptic drugs may cause worsening of epilepsy by aggravating pre-existing seizures or by triggering new seizure types. There are several reports of adverse effects related to midazolam, but only a few authors reported epileptic manifestations. We report four newborns seen at the Neonatal Intensive Care Unit of our University Hospital, who developed seizures a few seconds after the administration of midazolam. It is difficult to identify the patients at risk, but it is important to be aware and recognize this situation.